2007
DOI: 10.1002/jemt.20489
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Coatings Suppress Neutrophil Adhesion to a Polymeric Model Biomaterial

Abstract: Following our recent study on the fractionation, characterization, and model adsorption of mucins derived from bovine salivary glands (BSM), porcine stomach scrapings (PGM), and human whole saliva (MG1), we here present a microscopic evaluation of the interactions between mucin-coated substrates and human neutrophils. Our results show that surface-coating with BSM, PGM, and MG1 can be effectively used to suppress the adhesion of neutrophils to a polymeric model biomaterial (Thermanox). Neutrophil morphologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…In good agreement with our recent findings [16], the BSM, PGM and MG1 coatings were shown capable of effectively reducing the neutrophil activation normally following contact with the material surface (Fig. 2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In good agreement with our recent findings [16], the BSM, PGM and MG1 coatings were shown capable of effectively reducing the neutrophil activation normally following contact with the material surface (Fig. 2).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, we performed a microscopic evaluation of the interactions between human neutrophils and substrates of a polyethylene terephthalate-based model biomaterial (Thermanox) coated with the BSM, PGM and MG1 mucins, respectively [16]. Our results showed that all mucins could be used to effectively suppress the adhesion of neutrophils to the material surface.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…2,4,5 Additionally, cell membrane-tethered mucins have also been shown to play a role in cell signaling via tyrosine phosphorylation triggering, among other things, pathways involved in cellular motility and adhesion. 6 Apart from being a key component of mucus, mucins are employed to tailor various surface and interfacial properties of engineering systems too, such as surface hydrophilization, 7 antifouling, [8][9][10][11] surface coating models for drug delivery systems, 12 and lubrication. [13][14][15][16][17][18] Many of these studies employed hydrophobic substrates for the adsorption of mucins from aqueous 3 solutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, no criteria of selecting one type of mucin, e.g. BSM [7][8][9][10][11][12]16,17 or the other, i.e. PGM, [13][14][15] has been established in literature.…”
Section: Introductionmentioning
confidence: 99%